The Emergence of NMDA Receptor Metabotropic Function: Insights from Imaging - Dore, Kim; Aow, Jonathan; Malinow, Roberto (Frontiers in Synaptic Neuroscience, 2016)
The NMDA receptor (R) participates in many important physiological and pathological processes. For example, its activation is required for both long-term potentiation (LTP) and long-term depression (LTD) of synaptic transmission, cellular models of learning and memory. Furthermore, it may play a role in the actions of amyloid-beta on synapses as well as in the signaling leading to cell death following stroke. Until recently, these processes were thought to be mediated by ion-flux through the receptor. Using a combination of imaging and electrophysiological approaches, ion-flux independent functions of the NMDAR were recently examined. In this review, we will discuss the role of metabotropic NMDAR function in LTD and synaptic dysfunction.